PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP KARAKTER SISWA/I DI SMP IRA MEDAN - Khairul Amri Silalahi; Ahmad Rinalsi Siregar; Abdul Fattah Nasution (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to analyse the effect of Islamic Religious Education (PAI) on student character at IRA Medan Junior High School. The method used was quantitative descriptive correlation, with a sample of 35 students selected through purposive sampling technique. Data were collected using a closed questionnaire that measured the variables of Islamic Religious Education (X) and student character (Y). Before use, the research instruments were tested for validity and reliability, where the results showed that all items were valid and had a high level of reliability (Cronbach's Alpha > 0.7). Data analysis was conducted using normality test, R Square test, and T test to determine the significant relationship between the two variables. The results showed that PAI had a positive and significant influence on students' character, especially in the aspects of morality, discipline, responsibility, and social care. Therefore, the optimisation of Islamic Religious Education in the learning process, as well as support from schools, families, and communities, is needed to form a generation with noble character and high integrity.